PARMENIDES’ (BLUE) ORB - Stephen Curkpatrick (SAGACITY : Journal of Theology and Christian Education, 2021)
Parmenides’ seamless equidistant view of reality, interpreted epistemologically, anticipates the projection of human perceptions and values onto an impervious surface that remains unknowable in itself. Parmenides’ singular reality as an epistemological surface has an analogue in the contemporary image of our blue orb, the world, on which numerous projections are cast within human life. This article commences with Karl Popper’s observations of Parmenides as a necessary but mistaken view of cosmology and segues to epistemological possibilities expressed as projections of perception onto a Parmenidean idea of our world as a unity. Popper’s methodological conjecture and refutation informs a self-critical heuristic aspect to this scene as a source. The impetus of this study enhances the value of both Christian resources for human dignity and social principles of Pancasila toward social harmony and flourishing.